Turner syndrome: skin, liver, eyes, dental and ENT evaluation should be improved - Lam, Jenny; Stoppa-Vaucher, Sophie; Antoniou, Maria Cristina; Bouthors, Thérèse; Ruiz, Inge; Sekarski, Nicole; Rutz, Tobias; Fries, Sophie; Binz, Pierre Alain; Bütschi, Florence Niel; Vulliemoz, Nicolas; Gawlik, Aneta; et al. (Frontiers in Endocrinology, 2023)
Introduction: Turner syndrome association with multi-organ system comorbidities highlights the need for effective implementation of follow-up guidelines. We aimed to assess the adequacy of care with international guidelines published in 2007 and 2017 and to describe the phenotype of patients. Methods: In this multicenter retrospective descriptive cohort study, we collected growth and pubertal parameters, associated comorbidities, treatment, and karyotype in patients diagnosed at age <18 years between 1993 and 2022. We assessed age-appropriate recommendation follow-up (children, adolescents and adults) according to the 2007 guidelines if the last visit was before 2017 (18 recommendations) and the 2017 guidelines if the last visit was after 2017 (19 recommendations). Results: We included 68 patients followed at Lausanne University Hospital (n=64) and at Neuchatel Regional Hospital (RHNe) (n=4). 2.9% of patients underwent all recommended investigations. Overall, 68.9±22.5% and 78.5±20.6% of the recommendations were followed, before and after 2017 respectively. High implementation rates were found for height, weight and BMI (100%), cardiac (80 to 100%) and renal (90 to 100%) imaging. Low implementation rates were found for Ear, Nose and Throat (ENT) (56.5%), skin (38.5%), dental (23.1%), ophthalmological (10%) and cholestasis (0 to 29%) assessments, depending on age and time of visit. In adults (n=33), the mean proportion of followed recommendations was lower before than after 2017: 63.5±25.8% vs. 78.7±23.4%, p=0.039. Conclusions: Growth parameters, cardiac and renal imaging are well followed. However, efforts should be made for dental, ENT, ophthalmological, skin and cholestasis assessments. Adequacy of follow-up improved with the quality of transition to adult care. 1 * Bone disease referred to osteopenia, Léri-Weill dyschondrosteosis and cartilaginous protrusion of the ribs. ** Liver diseases were steatohepatitis with hepatomegaly for a 16 years and a 20 years old patient and inflammatory liver disease for a 30 years old patient.*** The p-values were calculated across 3 groups "Complete Monosomy X", "45,X Mosaicism" and "X Structural Rearrangement" with the Chi 2 test or with Fisher's exact test when Chi 2 test was not applicable.